2021
DOI: 10.1186/s13023-020-01635-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term experience with triheptanoin in 12 Austrian patients with long-chain fatty acid oxidation disorders

Abstract: Background Long-chain fatty acid oxidation disorders (LC-FAOD) are a group of rare inborn errors of metabolism with autosomal recessive inheritance that may cause life-threatening events. Treatment with triheptanoin, a synthetic seven-carbon fatty acid triglyceride compound with an anaplerotic effect, seems beneficial, but clinical experience is limited. We report our long-term experience in an Austrian cohort of LC-FAOD patients. Methods We retros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“… 6 , 7 Furthermore, triheptanoin has been studied clinically over 13 years, and the available literature provides clinical responses associated with LC‐FAODs. 8 , 9 , 10 , 11 , 12 , 13 …”
mentioning
confidence: 99%
“… 6 , 7 Furthermore, triheptanoin has been studied clinically over 13 years, and the available literature provides clinical responses associated with LC‐FAODs. 8 , 9 , 10 , 11 , 12 , 13 …”
mentioning
confidence: 99%
“…The reductions in the annualized rate and duration of MCEs were consistent with the results from the CL201 study 8,9 in triheptanoinnaïve patients (we also noted improvements in episodes and hospitalizations with triheptanoin compared with the CL201 study) and with reports of sustained efficacy reported in retrospective studies of triheptanoin, 4,19 including long-term triheptanoin treatment up to 16-19 years. 20,21 These encouraging results are important for clinicians and patients with LC-FAOD considering treatment with triheptanoin. In the interim analysis, there was a reduction in annualized total MCE event rate (70% median reduction) and duration (80% median reduction) in the triheptanoin-naïve group, with a mean study duration of 15.7 months.…”
Section: Discussionmentioning
confidence: 90%
“…In particular, C7 resulted in a higher ratio also for the species 40:2 of CER/HEX and for 42:1 of SM/HEX ( Figure 5 E,F). It is therefore conceivable that C7 may improve neuropathic symptoms via remodeling of complex lipids [ 31 , 32 , 33 , 34 ]. On the other hand, C8 showed a similar effect on the ratio for the species 34:1; however, all other species remained unaffected ( Figure 5 E,F).…”
Section: Resultsmentioning
confidence: 99%